We the poisoned : exposing the Flint water crisis cover-up and the poisoning of 100,000 Americans - Chariton, Jordan, 1986- (Rowan & Littlefield, an imprint of the Rowman & Littlefield Publishing Group, Inc., 2024)
"Based on eight years of reporting, thousands of confidential documents from the criminal investigation, and the former governor of Michigan's own words under oath, Jordan Chariton takes readers on the road to the crisis before the Flint River switch, when government officials allowed a nearly bankrupt Flint to borrow $100 million for a controversial new water system. As contaminated water flowed through Flint homes and residents grew sick, politicians intentionally and knowingly allowed residents to drink unhealthy water as they prioritized their own political ambitions and survival"--